High incidence of injury at the Sochi 2014 Winter Paralympic Games: a prospective cohort study of 6564 athlete days. Issue 17 (15th June 2016) - Derman, W; Schwellnus, M P; Jordaan, E; Runciman, P; Van de Vliet, P; Blauwet, C; Webborn, N; Willick, S; Stomphorst, J
Abstract : Objective: To describe the epidemiology of injuries at the Sochi 2014 Winter Paralympic Games. Methods: A total of 547 athletes from 45 countries were monitored daily for 12 days during the Sochi 2014 Winter Paralympic Games (6564 athlete days). Daily injury data were obtained from teams with their own medical support (32 teams, 510 athletes) and teams without their own medical support (13 teams, 37 athletes) through electronic data capturing systems. Results: There were 174 total injuries reported, with an injury incidence rate (IR) of 26.5 per 1000 athlete days (95% CI 22.7% to 30.8%). There was a significantly higher IR recorded in alpine skiing/snowboarding (IR of 41.1 (95% CI 33.7% to 49.6%) p=0.0001) compared to cross-country skiing/biathlon, ice sledge hockey or wheelchair curling. Injuries in the shoulder region were the highest single-joint IR (IR of 6.4 (95% CI 4.6% to 8.6%)), although total upper and lower body IR were similar (IR 8.5 vs 8.4 (95% CI 6.4% to 11.1%)). Furthermore, the IR of acute injuries was significantly higher than other types of injury onset (IR of 17.8 (95% CI 14.7% to 21.4%)). Conclusions: In a Winter Paralympic Games setting, athletes report higher injury incidence than do Olympic athletes or athletes in a Summer Paralympic Games setting. The highest incidence of injury was reported in the alpine skiing/snowboarding sporting category. There was a similar incidence of injury in the upper and lower limbs. The joint with the greatest rate of injury reported was the shoulder joint. Our data can inform injury prevention programmes and policy considerations regarding athlete safety in future Winter Paralympic Games.